Kesiapan Digital dan Adaptasi Pedagogis: Eksplorasi Tantangan Guru dalam Pemanfaatan Smart TV untuk Pembelajaran Digital di Konteks Rural dan Multikultural - Juriyah (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
The development of digital technology has brought significant changes to the field of education, including the utilization of Smart TVs as interactive learning media in elementary schools. This study aims to explore teachers’ digital readiness and analyze the forms of pedagogical adaptation in the use of Smart TVs for digital learning in rural and multicultural schools. This research employed a qualitative approach with a descriptive case study method. Data were collected through semi-structured interviews, observations, and documentation involving two teachers at SDIT Mutiara Insan, who were selected using a purposive sampling technique. Data analysis was conducted using thematic analysis, including data reduction, data presentation, theme categorization, and conclusion drawing. The findings revealed that Smart TVs were used to display instructional videos, interactive images, and digital presentations that enhanced students’ engagement and motivation in learning. However, teachers’ digital readiness remained at the basic to intermediate level, with limitations in mastering more complex learning applications as well as infrastructural challenges such as limited devices and internet access. Teachers’ pedagogical adaptation was reflected in the shift toward more interactive and student-centered learning methods. This study concludes that the successful implementation of Smart TVs is determined not only by the availability of technology, but also by teachers’ digital readiness, continuous training, and adequate school infrastructure support.